A Novel Adjuvant “Sublancin” Enhances Immune Response in Specific Pathogen-Free Broiler Chickens Inoculated with Newcastle Disease Vaccine - Yangke Liu; Jiang Zhang; Shuai Wang; Yong Guo; Tao He; Rui Zhou (Journal of Immunology Research)
Sublancin is a glycosylated antimicrobial peptide produced by Bacillus subtilis 168 possessing antibacterial and immunomodulatory activities. This study was aimed at investigating the effects of sublancin on immune functions and serum antibody titer in specific pathogen-free (SPF) broiler chickens vaccinated with Newcastle disease (ND) vaccine. For this purpose, 3 experiments were performed. Experiment 1: SPF broiler chicks (14 days old) were randomly allotted to 1 of 7 groups including a blank control (BC), vaccine control (VC), and 5 (3-7) vaccinated and sublancin supplemented at 5, 15, 30, 45, and 60 mg activity/L of water, respectively. Vaccinated groups (2-7) were vaccinated with ND vaccine by intranasal and intraocular routes at the 14th day. On 7, 14, 21, and 28 days post vaccination (dpv), the blood samples were collected for the determination of serum hemagglutination inhibition (HI) antibody titer. Experiment 2: SPF broiler chicks were divided into 1 of 3 groups, i.e., blank control (BC), vaccine control (VC), and sublancin treatment (ST). On 7, 14, and 21 dpv, the blood samples were collected for measuring HI antibody titer by micromethod. Experiment 3: the design of this experiment was the same as that of experiment 2. On 7 and 21 dpv, pinocytosis of peritoneal macrophages, B lymphocyte proliferation assay, measurement of CD4+ and CD8+ T cells, and serum cytokine quantitation were carried out. It was noted that sublancin promoted B lymphocyte proliferation, increased the proportion of CD8+ T lymphocyte subpopulations, and enhanced the antibody titer in broiler chickens. In addition, it was also observed that sublancin has the potential to induce the secretion of IFN-γ, IL-10, and IL-4. In conclusion, these findings suggested that sublancin could promote both humoral and cellular immune responses and has the potential to be a promising vaccine adjuvant.